Library information services in academic libraries of Azerbaijan: a comparative study. Issue 6 (12th August 2019) - Ismayilov, Khalil; Ismayilov, Nadir; Mammadova, Vafa
Abstract : Purpose: The purpose of this paper is to comparatively study the library and information services provided by three academic libraries – Baku State University Scientific Library, ADA University Library and Information Services and Khazar University Library and Information Center – located in Baku, Azerbaijan. Various types of library services are examined in terms of funding, acquisition and technical equipment support issues. Also, different subordination conditions (public/private) of the universities help to better understand the current position of academic libraries in different entities. Design/methodology/approach: Most part of the conveyed information was obtained through review of related literature, libraries' annual reports and personal communication with the directors of the academic libraries, to look for similarities and differences in provided library and information services. The results of the study are comparatively described through multiple tables and charts. Findings: For improving services it is necessary to develop paid forms of library and information services, maintain various training possibilities for library staff in modern librarianship areas, increase the variety and number of public and outreach activities. Research limitations/implications: As the findings of the paper suggest new forms of library services and activities, it is necessary to continue the topic in further studies to develop practical methods and applications for local library conditions. Originality/value: The paper can be accepted as the first comparative study of the library information services in academic libraries of Azerbaijan, which gives general overview and analysis of separate service ranges and types. The researchers interested in Azerbaijani librarianship may find it practical.